Pengaruh Brand Ambassador, Promosi dan Harga Terhadap Keputusan Pembelian - Sintia, Arna; Riyanto, Kuwat (ARBITRASE: Journal of Economics and Accounting, 2023)
The purpose of this study was to determine the effect of brand ambassadors, promotions, and prices on consumer purchasing decisions at Kopi Kenangan in North Cikarang. This type of research uses descriptive and verification methods which are carried out through data collection in the field. The research location was carried out in North Cikarang, precisely at Kopi Kenangan. The population is non probability sampling, so the technique for taking respondents is incidental. The sample used in this study was 100 people, namely all customers who visited Kopi Kenangan in North Cikarang and had purchased coffee or drinks sold at Kopi Kenangan outlets. The data collection used in this study was a questionnaire whose score was determined using a Likert scale. The data analysis method uses SmartPLS which is carried out in 3 (three) stages, including outer model analysis, inner model analysis, and hypothesis testing. The results of the study show that brand ambassadors  have a significant effect on purchasing decisions. Meanwhile, promotions have a significant influence on purchasing decisions. Brand ambassador, promotion, and price variables have an effect of 47.6%, where the remaining 52.4% is influenced by other variables outside of this study.